Evaluation and Improvement of The Effectiveness of Floating Pellets with Substitution of Chicken Feather Meal as Optimal Food for The Growth And Survival of Tilapia (Oreochromis niloticus) - Dimas Pratama; Dwi Tika Afriani; Emmy Syafitri (Universitas Labuhanbatu, 2024)
This study aims to determine the effectiveness of fishmeal substitution using chicken feather meal in pellets on growth, water quality, and survival of tilapia (Oreocromis niloticus), to determine the effectiveness of fishmeal substitution using chicken feather meal in pellets on FCR value, how the physical test value of floating pellets substituted with chicken feather meal, and what factors need to be updated in an effort to improve the quality of floating pellet feed substituted with chicken feather meal. The results of absolute growth research on fermented chicken feather meal pellets were 5.07 grams/head, non-fermented chicken feather meal pellets were 5.11 grams/head, and conventional pellets were 5.03 grams/head. While the results of absolute length growth on fermented chicken feather meal pellets were 3.21 cm/head, and absolute length growth for non-fermented chicken feather meal pellets was 3.24 cm/head, while for conventional pellets was 3.28 cm/head. The survival rate ranged from 62% - 68% during rearing with an FCR value of 0.6. Although the survival rate obtained was not good, the water quality during the study including pH, DO, and temperature showed good results in accordance with the quality standards. While the results of organoleptic observations of feed showed that the non-fermented artificial feed observed by the testers had a more pungent aroma than the fermented artificial feed, and conventional pellets tended to have a strong odor aroma. As for the texture assessment of the three types of feed, the dominant judge that all three have a hard texture